2022
DOI: 10.15452/cejnm.2021.12.0022
|View full text |Cite
|
Sign up to set email alerts
|

The Czech version of the Surgical Fear Questionnaire: measuring validity and reliability

Abstract: Aim:The aim of the study was to examine the psychometric properties of the Czech version of the Surgical Fear Questionnaire. Design: A cross-sectional study design. STROBE guidelines for reporting observational studies were followed for the study. Methods: The study sample consisted of 332 adult patients from the Czech Republic. The Surgical Fear Questionnaire (SFQ) was used to measure preoperative fear. Cronbach's alpha was calculated to test reliability. The construct validity of the SFQ was tested using exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
0
1
1
Order By: Relevance
“…No significant difference was noted between the male and female patients in our study. However other studies have observed an increase in fear associated with the female gender (12). Increasing age was found to be a factor which increases fear of surgery in multiple studies (1,12) including this study.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…No significant difference was noted between the male and female patients in our study. However other studies have observed an increase in fear associated with the female gender (12). Increasing age was found to be a factor which increases fear of surgery in multiple studies (1,12) including this study.…”
Section: Discussioncontrasting
confidence: 38%
“…There have been attempts to quantify surgical fear. The Surgical Fear Questionnaire (SFQ) is a tool that is used to quantify surgical fear and has been validated in many different languages and used in many research publications worldwide (11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…Only 1.5% of patients indicated to not experience any fear with respect to short-and long-term aspects of their upcoming treatment. This represents a novel insight, as the commonness of fear of surgery has neither been addressed in prior studies on female BC patients, nor in those on other surgical samples [21,22,24,[28][29][30][31][50][51][52][53][54][55][56][57][58][59]. In view…”
Section: Discussionmentioning
confidence: 99%
“…The detailed requirements for calculating the SFQ scores undoubtedly constitute its advantage, as they ensure high reliability of the data obtained. The discussed questionnaire has satisfactory psychometric properties, allowing for its use both in clinical practice and scientific research [28][29][30][31][32][33].…”
Section: The Surgical Fear Questionnairementioning
confidence: 99%
“…A preliminary study conducted among 65 patients awaiting cardiac surgery provided promising results regarding the reliability of the scale (Cronbach's a coefficient for the full scale was 0.93, for short-term aspects of surgery was 0.91, and for long-term surgery aspects was 0.90). The SFQ questionnaire has been used in studies conducted in the Netherlands [28,29], Greece [34], Portugal [35,36], Turkey [21,23,33,[37][38][39][40][41][42][43], Croatia [44], Norway [45], Germany [31], Italy [46], Czech Republic [30], China [32], United States [47,48], Ireland [49], and Hungary [50][51][52]. Most of these publications appeared in the years 2022-2023.…”
Section: Prospective Evaluation Monitoring the Level Of Anxietymentioning
confidence: 99%